2011
DOI: 10.4061/2011/536735
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in Acquired Factors Related to Postmenopausal Osteoporosis and Sarcopenia

Abstract: Postmenopausal population is at increased risk of musculoskeletal impairments. Sarcopenia and osteoporosis are associated with significant morbidity and social and health-care costs. These two conditions are uniquely linked with similarities in pathophysiology and diagnostic methods. Uniform diagnostic criteria for sarcopenia are still evolving. Postmenopausal sarcopenia and osteoporosis share many environmental risk- and preventive factors. Moreover, geriatric frailty syndrome may result from interaction of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 216 publications
1
45
0
6
Order By: Relevance
“…The mechanical load may lead to bone strengthening with mobility-induced weight-bearing stress [3]. Thus, our results are in accordance to previous studies that demonstrated that weight loss may increase the bone turnover, suggesting that body weight enhances the differentiation of osteoblasts and increase osteoblastic bone formation besides attenuates osteoclastic activity [13,14,15,18].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The mechanical load may lead to bone strengthening with mobility-induced weight-bearing stress [3]. Thus, our results are in accordance to previous studies that demonstrated that weight loss may increase the bone turnover, suggesting that body weight enhances the differentiation of osteoblasts and increase osteoblastic bone formation besides attenuates osteoclastic activity [13,14,15,18].…”
Section: Discussionsupporting
confidence: 82%
“…Beyond the bone mass decline, decrements on blood levels of oestrogen also may cause age-related muscle mass loss [1,3,7,8]. According to previous studies the relative muscle skeletal index (RMSI) reduces approximately 1.1 kg/decade [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, notwithstanding enthusiastic reviews relating vitamin D status to muscle strength and function (80,81) , in addition to the cautious approach of the IOM report in relation to vitamin D status and muscle function there are two other important issues that need to be resolved.…”
Section: Vitamin D: Strength Preservation In Musclementioning
confidence: 99%